Prevalence and Clinical Profile of Drug Eruptions among Antiretroviral Therapy-Exposed HIV Infected People in Yaoundé, Cameroon - Kouotou, Emmanuel Armand (Dermatol Res Pract, 2017)
BACKGROUND: Prevalence and incidence of drug eruptions vary around the world and are influenced by some key factors including HIV infection. OBJECTIVE: This study aimed to find the peculiarities of drug eruptions in people living with HIV (PLHIV) and on antiretroviral therapy (ART). METHODS: This was a retrospective cross-sectional study including ART-taking PLHIV, aged 15+ years, followed up between January 2010 and December 2014 at the day-care unit of the Yaoundé Central Hospital, and who presented with drug eruptions after ART initiation. RESULTS: Of 6,829 ART-experiencing PLHIV, 41 presented with drug eruptions, giving a prevalence of 0.6%. The M/F sex ratio equaled 0.17. The mean age was 41.07 ± 11.36 years. Benign drug eruptions accounted for 83.3%. Milder forms were essentially maculopapular exanthema (36.6%), fixed pigmented erythema (7.3%), and urticaria (4.9%). Severe forms were represented by multiform erythema (4.9%), toxic epidermal necrolysis (2.4%), and drug hypersensitivity syndrome (2.4%). The Zidovudine + Lamivudine + Efavirenz ART-protocol was received by 48.8% of patients and 69% of patients were receiving Cotrimoxazole prophylaxis. Nevirapine, Efavirenz, Zidovudine, and Cotrimoxazole were suspected as the potential causes in 43.7%, 4.8%, 2.4%, and 26.8% of cases, respectively. CONCLUSION: Drug eruptions seem infrequent among ART-exposed HIV infected adult Cameroonians.